Effect of neonatal breast crawl on breastfeeding: a prospective cohort study - Pang, Yan; Wang, Xin; Li, Huimin; Tu, Suhua (Frontiers in Pediatrics, 2023)
Aim:To analyse the effect of breast crawl on neonatal breastfeeding within 5 months of delivery. Design:Prospective Cohort Study. Methods: Neonates were divided into successful and failed groups, according to whether the newborn crawled to the breast and began sucking for the first time within 1 h of delivery. The initiation of lactation and breastfeeding duration of the two groups were analysed at 24 h, 48 h, 72 h, the feeding practices were followed-up on the 7th day, 42nd day, and 5th month in order to explore the long-term benefits of breast crawl on breastfeeding. Results: A total of 163 neonates were included. The initiation time and the duration of first feeding, the lactation initiation in the successful group was earlier, the scores of first and in-hospital breastfeeding scales were higher. Public Contribution:Breast crawl is the preferred method for mothers to begin breastfeeding their neonates.The delivery room is the place where the first breast crawl occurs immediately after delivery. The midwife is the key person to protect this valuable behavior. Therefore, the midwife needs provide valuable opportunities for the breast crawl of the newborn and promote this behavior.